Influence of Environmental and Social Programs on Dimensionality of Triple Bottom Line of Manufacturing SMEs in South Africa - Qeke, S.R; Dubihlela, J (Online, 2018)
Over the past decades manufacturing SMEs have played a very crucial role as a driving force behind socio-economic growth and industrial development, acting as prime agents of change and growth of emerging economies. Manufacturing SMEs are endowed with potential for providing opportunities and eradicating poverty in a more sustainable manner, with great potential for more active environmental and social programs. In spite of that, manufacturing SMEs in emerging markets such as South Africa are still struggling and battling with issues of sustainability. The triple bottom line (TBL) framework has guided many firms operating in the lenses of sustainability by reporting, accounting and taking responsibility for environmental and social sensitivity with their operations. This paper explored the avenues through which manufacturing SMEs utilize the TBL framework as a reporting tool to measure their performance. This paper analyses opportunities and challenges of incorporating the social and environmental dimensions of the triple bottom line for SMEs. The study applies a quantitative design on a purposively selected sample of 200 respondents that were considered as decisionmakers of manufacturing SMEs in Cape Town. The researcher administered questionnaires to the directors of operations, supervisors, owners and managers. These are respondents at decision-making equivalent positions in manufacturing SMEs. These respondents were deemed best suited to report the decisions made regarding the operational strategy and the results of the environmental and social programs implemented by manufacturing SMES.
Full text
Keywords: Triple bottom line, Sustainability, Environmental & Social programs, Manufacturing SMEs, South Africa, JEL Classification: O31, O32, O33